2021
DOI: 10.1155/2021/2676745
|View full text |Cite
|
Sign up to set email alerts
|

KIF11 Promotes Proliferation of Hepatocellular Carcinoma among Patients with Liver Cancers

Abstract: Background. Hepatocellular carcinoma (HCC) lacks effective treatments and has a poor prognosis. Therefore it is needed to develop more effective drug targets. Kinesin family member 11 (KIF11) has been reported to affect the progression of several cancers, and its high expression associates with the prognosis of patients. However, the relevant mechanisms of KIF11 in HCC progression have not been studied. Method. Through the cancer genome atlas (TCGA) database and immunohistochemical (IHC) staining of patients’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…It is simply described to be closely related to the tumor microenvironment [15][16][17][18]. AURKA and KIF11 are used as a target in many tumors for targeted therapy, and these genes are also microenvironment constituent genes of tumors [19][20][21][22]. CKD1 has not been studied much in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…It is simply described to be closely related to the tumor microenvironment [15][16][17][18]. AURKA and KIF11 are used as a target in many tumors for targeted therapy, and these genes are also microenvironment constituent genes of tumors [19][20][21][22]. CKD1 has not been studied much in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of KIF11 can lead to abnormal cell division and genomic instability, which are closely related to tumorigenesis (27). Studies have found that abnormal expression of KIF11 is closely related to HCC progression and prognosis, indicating that it could be a biomarker for the prognosis and treatment of HCC (28). PBK is a T cell-derived protein kinase, belonging to the serine/threonine protein kinase, with high expression in the testis and thymus and low expression in normal cells (29).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, Huang et al also demonstrate that IGF1 could be the carcinogenic factor and possible target in HC by bioinformatic method and experiments [ 38 ]. Both KIF11 and ZWINT can affect HC progression by mediating cell proliferation [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%